Systemic Sclerosis Associated Interstitial Lung Disease: A Comprehensive Overview - Mackintosh, John A.; Stainer, Anna; Barnett, Joseph L.; Renzoni, Elisabetta A. (Seminars in Respiratory and Critical Care Medicine, 2019)
Interstitial lung disease (ILD) is a common complication of systemic sclerosis (SSc). SSc-ILD adversely impacts quality of life and is currently the leading cause of death in this multisystem disease. Identifying clinically significant SSc-ILD is critically important. Accurate staging and prognostication remain difficult; however, significant advances have been made in the last decade. Evidence supports the need to treat patients with extensive and/or progressive SSc-ILD, while only a subset of patients with limited ILD may require treatment. Research is urgently required to allow improved prediction of patients at risk of ILD progression at an early point in the disease, and ideally prior to its onset, to allow prevention. The last decade has seen the publication of landmark clinical trials for SSc-ILD. More effective strategies with less toxicity are under investigation. For those with refractory or very advanced disease, studies into disease-specific palliative approaches are in their infancy. Lung transplantation as an option for SSc-ILD remains patient- and center-specific, with data to suggest equivalent outcomes to other fibrotic lung diseases, in carefully selected cases. This review aims to provide a comprehensive overview of all key aspects of SSc-ILD.
Keywords: systemic sclerosis; scleroderma; interstitial lung disease; pulmonary fibrosis